2020
DOI: 10.1002/hup.2760
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between suicide rate and antidepressant prescription: An ecological study in the People's Republic of China

Abstract: ObjectivesThe objective of this study was to estimate the features of suicide rate and its association with antidepressant prescriptions during the past decade in China.MethodsOfficial data on suicides were obtained and stratified by four age groups, gender, urban/rural areas, and regions (East, Central, and West). The annual antidepressant prescriptions were expressed in pills per 100 persons calculated as the volume of prescriptions divided by the total population. Negative binomial regression was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Furthermore, according to the psychological autopsy of suicide conducted on adults in Korea, it was estimated that 619 out of 698 included individuals who died by suicide (88.7%) had psychiatric disorders ( 40 ). 5 A Chinese psychological autopsy study found that 63% of all suicides were related to mental illness ( 41 ), and it was recently found that antidepressant use is associated with a low suicide rate ( 42 ). Studies on suicide in children and adolescents reveal that mental illness is an important risk factor for suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to the psychological autopsy of suicide conducted on adults in Korea, it was estimated that 619 out of 698 included individuals who died by suicide (88.7%) had psychiatric disorders ( 40 ). 5 A Chinese psychological autopsy study found that 63% of all suicides were related to mental illness ( 41 ), and it was recently found that antidepressant use is associated with a low suicide rate ( 42 ). Studies on suicide in children and adolescents reveal that mental illness is an important risk factor for suicide.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) has recognized the urgent need to reduce suicide-related mortality on an international scale. Understanding the diverse causes of suicide is crucial, with research identifying genetic, economic, biological, psychological, social, and cultural factors, among others (Xin et al, 2021). Moreover, suicide not only devastates the individuals who die but also leaves behind emotional turmoil for suicide survivors, often resulting in long-lasting effects and potentially leading to their own suicidal tendencies (Pompili et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The persistent challenges posed by rising suicide rates, despite ongoing mental health efforts, demand immediate attention (World Health Organization, 2021). It is crucial to comprehend the underlying causes and barriers to effective prevention in order to develop targeted interventions (Xin et al, 2021). By understanding the complexities surrounding suicide and its contributing factors, comprehensive approaches can be formulated to reduce stigma, enhance access to mental health services, and provide vital support to at-risk individuals (Mortier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%